Penerapan Model Pembelajaran Langsung Berbantuan Media Gambar Seri untuk Meningkatkan Keterampilan Menulis Karangan Narasi Peserta Didik Kelas IV-B SDN 5 Panarung Tahun Pelajaran 2016/2017: Application of Direct Learning Model Assisted by Media Drawings Series to Improve Narrative Essay Writing Skills of Class IV-B Students of SDN 5 Panarung 2016/2017 Academic Year - Diplan Diplan; Siti Astuti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to describe learning activities and improve Narrative Essay Writing Skills by using a direct learning model assisted by following image media of IV-B class students at SDN 5 Panarung. The type of this research is PTK research with the subject of all class IV-B students at SDN 5 Panarung, amounting to 24 people. Data collection techniques in this study used tests and observations. Data analysis used qualitative data and quantitative data. The results of this study indicate that: (1) the activity of students increases during the learning process of Indonesian language by using a direct learning model assisted by media drawing series with an average of 3.7 in perfect criteria. (2) The narrative essay writing skill increases this can be seen from the initial test with an average of 67.0 with classical completeness of 33.33%, the cycle I with an average of 72.16 with the artistic integrity of 87.5%. This shows that learning can be said to be successful and exceeds classical completeness which is 85%.